Tree–shrub–grass composite woodland better facilitates emotional recovery in college students emotion better than other plant communities - Fu, Wen Jun; Gao, Fei; Zhang, Xing; Dong, Bo; Chen, Xi Lin; Xu, Xin; Yang, Zhi Yu; Liu, Yong (Frontiers in Psychology, 2024)
The rapid development of urbanization is gradually reducing opportunities for human beings to interact with the natural environment, and environmental pressures have brought about many additional negative emotions for humans. Among them, the mental health problems of college students should be given social attention. Previous research has indicated that natural landscapes exhibit a greater capacity for ameliorating negative emotional states in individuals when compared to urban landscapes. Nevertheless, significant scientific inquiries, such as the uniformity of the rejuvenating effect across distinct categories of natural landscapes and the choice of the optimal plant community for achieving the most potent restorative effect, remain unexplored. This study aimed to address these questions by selecting four plant communities (single-layer grassland, single-layer woodland, tree-grass composite woodland, tree-shrub-grass composite woodland) and using an electroencephalography method to capture the neuroelectric activity of the participants in combination with the Positive and Negative Affect Schedule score to explore the effects of plant community types on emotional recovery. Our results showed that all four plant communities significantly increased positive emotions and significantly reduced negative emotions. Specifically, there was no significant difference in the recovery effect of positive emotions among the four plant community types, but there was a significant difference in the recovery effect of negative emotions. The negative emotion-recovery effect of tree-shrub-grass composite woodland was significantly better than that of tree-grass composite woodland, single-layer grassland, and single-layer woodland, respectively. The electroencephalography findings demonstrated congruence with the behavioral outcomes, revealing a marked elevation in the power of the alpha frequency band within the brain induced by exposure to the tree-shrub-grass composite woodland when compared to exposure to the tree-grass composite woodland, single-layer grassland, and single-layer woodland conditions. The outcomes underscore the superior rejuvenation efficacy of the tree-shrub-grass composite woodland, thereby yielding substantial ramifications for the realms of landscape planning and design.